Effect of stage‐based education provided by dedicated dietitians on hyperphosphataemic haemodialysis patients: results from the Nutrition Education for Management of Osteodystrophy randomised controlled trial. Issue 5 (21st March 2017) - Rizk, R.; Karavetian, M.; Hiligsmann, M.; Evers, S. M. A. A.
Abstract: Background: The Nutrition Education for Management of Osteodystrophy trial showed that stage‐based nutrition education by dedicated dietitians surpasses existing practices in Lebanon with respect to lowering serum phosphorus among general haemodialysis patients. The present study explores the effect of nutrition education specifically on hyperphosphataemic patients from this trial. Methods: Hyperphosphataemic haemodialysis patients were allocated to a dedicated dietitian (DD), a trained hospital dietitian (THD) and existing practice (EP) protocols. From time‐point ( t )‐0 until t ‐1 (6 months), the DD group ( n = 47) received 15 min of biweekly nutrition education by dedicated dietitians trained on renal nutrition; the THD group ( n = 89) received the usual care from trained hospital dietitians; and the EP group ( n = 42) received the usual care from untrained hospital dietitians. Patients were followed‐up from t ‐1 until t ‐2 (6 months). Analyses used two‐way repeated measures analysis of variance and Cohen's effect sizes ( d ). Results: At t ‐1, phosphataemia significantly decreased in all groups (DD:−0.27 mmol L −1 ; EP:−0.15 mmol L −1 ; THD:−0.12 mmol L −1 ; P < 0.05); the DD protocol had the greatest effect relative to EP ( d = −0.35) and THD ( d = −0.50). Only the DD group showed more readiness to adhere to a low phosphorus diet at t ‐1; although, at t ‐2, this regressed to baseline levels. The malnutrition inflammation score remained stable only in the DD group, whereas the EP and THD groups exhibited a significant increase (DD: 6.74, 6.97 and 7.91; EP: 5.82, 8.69 and 8.13; THD: 5.33, 7.92 and 9.42, at t ‐0, t ‐1 and t ‐2, respectively). Conclusions: The results of the present study suggest that the DD protocol decreases serum phosphorus compared to EP and THD, at the same time as maintaining the nutritional status of hyperphosphataemic haemodialysis patients. Assessing the cost‐effectiveness of the DD protocol is recommended.